Establishing a Framework for the Clinical Translation of Germline Findings in Precision Oncology. Issue 5 (29th May 2020) - Dixon, Katherine; Young, Sean; Shen, Yaoqing; Thibodeau, My Linh; Fok, Alexandra; Pleasance, Erin; Zhao, Eric; Jones, Martin; Aubert, Geraldine; Armstrong, Linlea; Virani, Alice; Regier, Dean; et al.
Abstract: Inherited genetic variation has important implications for cancer screening, early diagnosis, and disease prognosis. A role for germline variation has also been described in shaping the molecular landscape, immune response, microenvironment, and treatment response of individual tumors. However, there is a lack of consensus on the handling and analysis of germline information that extends beyond known or suspected cancer susceptibility in large-scale cancer genomics initiatives. As part of the Personalized OncoGenomics program in British Columbia, we performed whole-genome and transcriptome sequencing in paired tumor and normal tissues from advanced cancer patients to characterize the molecular tumor landscape and identify putative targets for therapy. Overall, our experience supports a multidisciplinary and integrative approach to germline data management. This includes a need for broader definitions and standardized recommendations regarding primary and secondary germline findings in precision oncology. Here, we propose a framework for identifying, evaluating, and returning germline variants of potential clinical significance that may have indications for health management beyond cancer risk reduction or prevention in patients and their families.